Okra Growth by Using Tamarind as Organic Fertilizer - Muhammad Najmi Abd. Hadi; Muhammad Hazim Hasnan; Nurul Afiz Che Hasan; Nor Farah Atiqah Ahmad (Multidisciplinary Applied Research and Innovation, 2024)
Agronomic practices using different organic materials help in improving soil fertility and the quality of produce. Nitrogen (N) and phosphorus (P) are both essential nutrients required for plant growth and development. The level of nitrogen and phosphorus can significantly affect the growth rate of plants. This study aims to investigate the effectiveness of tamarind seed and tamarind fruit shell as organic fertilizer for Okra plant growth. By using Energy Dispersive X-ray Spectrometer (EDS) and Scanning Electron Microscopy (SEM) image, the presence of the element nitrogen (N) was only present in the tamarind shell by 9.65%. The growth for length and diameter is prominent by tamarind seed as fertilizer and for thickness, the tamarind shell has increased the growth by 43.4%. From this study, it can be concluded that the element nitrogen may not contribute to the overall growth of a plant but rather to certain criteria. This study offered important insights into the results of the composting project and offer suggestions for future composting and sustainable waste management initiatives.